2004
DOI: 10.1073/pnas.0306552101
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of anthrax edema factor by adefovir, a drug for chronic hepatitis B virus infection

Abstract: Edema factor (EF), a key virulence factor in anthrax pathogenesis, has calmodulin (CaM)-activated adenylyl cyclase activity. We have found that adefovir dipivoxil, a drug approved to treat chronic infection of hepatitis B virus, effectively inhibits EF-induced cAMP accumulation and changes in cytokine production in mouse primary macrophages. Adefovir diphosphate (PMEApp), the active cellular metabolite of adefovir dipivoxil, inhibits the adenylyl cyclase activity of EF in vitro with high affinity (Ki ‫؍‬ 27 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 41 publications
4
108
0
Order By: Relevance
“…We next confirmed that the effects of ET and LT on DC were due to the enzymatic activities of EF and LF using the following specific chemical inhibitors: adefovir dipivoxil (Bis-POM-PMEA) (24) and EGCG, respectively (25). We found that preincubation with Bis-POM-PMEA restored TNF-␣ and IL-12p70 secretions by ET-treated DC to normal levels (Fig.…”
Section: Et and Lt Inhibitors Restore DC Cytokine Secretionsupporting
confidence: 64%
See 1 more Smart Citation
“…We next confirmed that the effects of ET and LT on DC were due to the enzymatic activities of EF and LF using the following specific chemical inhibitors: adefovir dipivoxil (Bis-POM-PMEA) (24) and EGCG, respectively (25). We found that preincubation with Bis-POM-PMEA restored TNF-␣ and IL-12p70 secretions by ET-treated DC to normal levels (Fig.…”
Section: Et and Lt Inhibitors Restore DC Cytokine Secretionsupporting
confidence: 64%
“…6, B and C). The affinity of adefovir diphosphate, the active cellular metabolite of Bis-POM-PMEA for EF-calmodulin complex, is 10-to 500-fold higher than for mammalian host adenylyl cyclase (24); EGCG has been shown to have no toxicity even at concentrations exceeding 100 M in rats and humans (25). The low concentrations used in these experiments and the absence of cell toxicity suggest a specific interaction between inhibitors and their respective targets.…”
Section: Et and Lt Inhibitors Restore DC Cytokine Secretionmentioning
confidence: 87%
“…In addition, 2Ј,3Ј-(2,4,6-trinitrophenyl) (TNP)-substituted NTPs are potent inhibitors of mammalian AC (Mou et al, 2006). Furthermore, adefovir, a drug for the treatment of chronic hepatitis B virus infection, is a potent CyaA inhibitor (Shen et al, 2004).…”
mentioning
confidence: 99%
“…It is able to enter into eukaryotic cells where it is activated upon binding to endogenous calmodulin (CaM) to produce supraphysiological levels of cAMP that alter the cell physiology. By targeting immune cells, EF contributes to the virulence of B. anthracis and is therefore considered as a target for anti-anthrax drugs (25)(26)(27)(28).…”
mentioning
confidence: 99%